1999
DOI: 10.1046/j.1365-2958.1999.01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial transcription factors involved in global regulation

Abstract: SummaryThe presence of intricate global cell regulation mechanisms may be one reason for the exceptional environmental and evolutionary success of microbes. Promoters, the cis-acting signals, are responsive to several stimuli related to growth, stress and substrate speci®city. Their response is mediated by a wide variety of trans-acting regulators that sense the environment and the physiological state of the cell and adjust the transcription of speci®c genes. One of the main transcriptional regulation webs ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…In addition, at least two transcriptional activators -SdiA, which is a part of a quorum-sensing pathway, and RcsB, which is involved in the regulatory pathway of capsular polysaccharide biosynthesis -have been found to modulate ftsZ expression (reviewed by Vicente et al, 1999). In B. subtilis, three promoter sequences for ftsZ expression were identified, and our results show that YycF is the transcriptional factor with the potential to regulate ftsZ expression.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, at least two transcriptional activators -SdiA, which is a part of a quorum-sensing pathway, and RcsB, which is involved in the regulatory pathway of capsular polysaccharide biosynthesis -have been found to modulate ftsZ expression (reviewed by Vicente et al, 1999). In B. subtilis, three promoter sequences for ftsZ expression were identified, and our results show that YycF is the transcriptional factor with the potential to regulate ftsZ expression.…”
Section: Discussionmentioning
confidence: 73%
“…The assigned sequences for the UP element (AAAACATTTTTTTGGTGAAGTT) scored an 86% homology to the UP element consensus sequences of the promoters recognized by the ␣-CTD of the RNAP in E. coli (39). It has been suggested that class I activators stimulate transcription with promoters by contacting the ␣-subunit of RNAP (40). However, it seems likely that 220 and 198 bp upstream of the transcription start site are still unusually large distances for class I activation of promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies of different S -dependent promoters suggest that other parameters such as increased intracellular salt concentration, degree of DNA supercoiling, the ppGpp alarmone, and modulation by trans-acting regulators all contribute to S selectivity (reviewed in Refs. [11][12][13][14][15]. The main sequence feature specific for S -dependent promoters would be a C nucleotide immediately upstream of the Ϫ10 promoter element (CTATA(c/a)T at the Ϫ13 position relative to the transcription start (Ϫ13C)); the Ϫ35 element does not appear to be important for promoter recognition by S , although conflicting data on its role have been reported (10, 16 -19).…”
mentioning
confidence: 99%